Identity incongruent discrimination, racial identity, and mental health for multiracial individuals. Issue 1 (2nd January 2021) - Franco, Marisa; Toomey, Thomas; DeBlaere, Cirleen; Rice, Kenneth
ABSTRACT: The current study sought to explore the unique roles of traditional and identity incongruent discrimination (discrimination aimed at a perceived racial identity that does not match self-identity) in predicting racial identity and mental health for Multiracial people. Multiracial individuals ( N =  472) took measures of discrimination, racial identity, and mental health via Qualtrics. A confirmatory factor analysis confirmed the separateness of traditional and identity incongruent discrimination. A model – framed by the minority stress theory – was then tested in which traditional and incongruent discrimination predicted indexes of negative internal racial identity variables and mental health. Findings indicated that incongruent discrimination predicted racial identity detachment, but not mental health beyond traditional discrimination. Contrastingly, traditional discrimination directly influenced mental health, but exhibited non-significant relationships with negative internal racial identity variables.